Phylogeography of West Nile Virus: from the Cradle of Evolution in Africa to Eurasia, Australia, and the Americas - May, Fiona J. (American Society for Microbiology (ASM), 2011)
West Nile virus (WNV) is the most widely distributed of the encephalitic flaviviruses and is a major cause of encephalitis, with isolates obtained from all continents, apart from Antarctica. Subsequent to its divergence from the other members of the Japanese encephalitis virus complex, presumably in Africa, WNV has diverged into individual lineages that mostly correspond with geographic distribution. Here we elucidate the phylogeography and evolutionary history of isolates from lineage 1 of WNV. Interestingly, there are many examples of the same amino acid having evolved independently on multiple occasions. In Africa, WNV exists in an endemic cycle, whereas it is epidemic in Europe, being reintroduced regularly from Africa either directly (in western Europe) or via the Middle East (in eastern Europe). Significantly, introduction into other geographic areas has occurred on one occasion only in each region, leading to subsequent establishment and expansion of the virus in these areas. Only one endemic genotype each is present in India and Australia, suggesting that WNV was successfully introduced into these locations once only. Each introduction occurred many centuries ago, probably due to trade and exploration during the 19th century. Likewise, in the Americas, WNV was successfully introduced in 1999 and subsequently became endemic across most temperate regions of North America (NA). In contrast to previous suggestions, an isolate from the epidemic in Israel in 1998 was not the direct progenitor of the NA epidemic; rather, both epidemics originated from the same (unknown) location.